2018
DOI: 10.1021/acs.est.8b03304
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Regeneration of Manganese Oxide-Coated Sand for Oxidation of Organic Stormwater Contaminants

Abstract: Urban stormwater, municipal wastewater effluent, and agricultural runoff contain trace amounts of organic contaminants that can compromise water quality. To provide a passive, low-cost means of oxidizing substituted phenols, aromatic amines, and other electron-rich organic compounds during infiltration of contaminated waters, we coated sand with manganese oxide using a new approach involving the room-temperature oxidation of Mn with permanganate. Manganese oxide-coated sand effectively oxidized bisphenol A und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 71 publications
1
38
0
Order By: Relevance
“…180 Recently, manganese oxide-coated sand has been proposed as cost-effective and regenerative geomedia for stormwater treatment to target the removal of hyphil-TrOCs. 181,182 Grebel et al 181 observed that birnessite (a layered MnO 2 ) was highly reactive towards aromatic compounds with electron-donating moieties (e.g., BPA and 2-mercaptobenzothiazole) and moderately reactive towards compounds with electron-withdrawing functional groups (e.g., diuron) or steric hindrance at the most likely reaction site (e.g., prometon). However, birnessite was unreactive towards numerous other hyphil-TrOCs (e.g., TCPP, benzotriazole, and fipronil).…”
Section: Metal Oxide Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…180 Recently, manganese oxide-coated sand has been proposed as cost-effective and regenerative geomedia for stormwater treatment to target the removal of hyphil-TrOCs. 181,182 Grebel et al 181 observed that birnessite (a layered MnO 2 ) was highly reactive towards aromatic compounds with electron-donating moieties (e.g., BPA and 2-mercaptobenzothiazole) and moderately reactive towards compounds with electron-withdrawing functional groups (e.g., diuron) or steric hindrance at the most likely reaction site (e.g., prometon). However, birnessite was unreactive towards numerous other hyphil-TrOCs (e.g., TCPP, benzotriazole, and fipronil).…”
Section: Metal Oxide Materialsmentioning
confidence: 99%
“…181 Stormwater constituents such as dissolved organic matter or inorganic ions (e.g., calcium or carbonate) can contribute to exhaustion of the redox reactivity of manganese oxide-coated sands. 181 Charbonnet et al 182 found that exhausted manganese oxide-coated sand could be regenerated with HOCl leading to similar reactivity and longevity than the pristine MnO 2 . Geomedia regeneration in the field could be a main advantage as it prevents excavation of the exhausted material, reduces disposal costs, and helps to overcome implementation barriers.…”
Section: Metal Oxide Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of organic contaminants by manganese oxides is an important reaction that influences contaminant fate in aqueous systems (Duckworth et al., 2017; Grebel, Charbonnet, & Sedlak, 2016; Li, Zhang, Ertunc, Schaeffer, & Ji, 2012; Post, 1999; Remucal & Ginder‐Vogel, 2014; Sim, Lee, Lee, Choi, & Oh, 2009; Siqueira, Nair, Hammerschmidt, Safir, & Putnam, 1991; Wang & Giammar, 2015). Because of their oxidative reactivity, manganese oxides have been proposed for passive water treatment for contaminants in urban stormwater runoff, green infrastructure, or water from contaminated sources (Charbonnet et al., 2018; Grebel et al., 2013, 2016; Huang et al., 2018; Klausen, Haderlein, & Schwarzenbach, 1997; Luthy & Sedlak, 2017; Pizzigallo, Ruggiero, Crecchio, & Mascolo, 1998; Shaikh et al., 2016; Stone, 1987; Stone & Morgan, 1984; Tebo et al., 2004; Ulrich & Stone, 1989). Here, we determine that surface‐bound cations, which include both sorbed and interlayer cations, have a large effect on manganese oxide reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds used in this study include bisphenol A (BPA), 5-chloro-2-(2,4-dichlorophenoxy) phenol (triclosan), estrone, and 4-methylphenol (p-cresol) (Supplemental Figure S1). Phenolic compounds such as these are found in wastewater effluents that discharge into natural ecosystems (Bina, Mohammadi, Amin, Pourzamani, & Yavari, 2018;Bulloch et al, 2015;Charbonnet, Duan, van Genuchten, & Sedlak, 2018;Grebel et al, 2013Grebel et al, , 2016Huang, Zhong, Dai, Liu, & Zhang, 2018;Lin, Liu, & Gan, 2009b;Luthy & Sedlak, 2017;Montes-Grajales, Fennix-Agudelo, & Miranda-Castro, 2017;Yang, Ok, Kim, Kwon, & Tsang, 2017) and serve to show any differences in cation effects due to phenolic structure (Trainer, Ginder-Vogel, & Remucal, 2020). Cations can inhibit the reaction rate of phenols with manganese oxides (Remucal & Ginder-Vogel, 2014), which has implications for environmental oxidative degradation of phenolic contaminants because cations are ubiquitous in natural systems.…”
Section: Introductionmentioning
confidence: 99%